Voluntary Contributions to the Establishment and Operation of Public Goods: Theory and Experimental Evidence - Yuval Arbel; Ronen Bar-El; Mordechai E. Schwarz; Yossi Tobol (Institute for the Study of Labor (IZA), 2014)
We study the dynamics of the private provision of a public good that requires both capacity buildup and ongoing operating costs. We show that setting a time limit for the collection of contributions dedicated to capacity buildup minimizes the utility loss at the Nash equilibrium. We test the theoretical model empirically by conducting contribution game experiments with religious Jewish students for the procurement of sustainable supplies for their campus synagogues and ongoing operations. The empirical findings support the model's prediction and demonstrate that the theory fairly describes the pattern of contributions when the group of contributors attributes high intrinsic value to the public good. More specifically, we find that total contributions increase over time, contributions to the capacity buildup increase with the time limit and with the number of contributors, and contributions to the capacity buildup decrease with ongoing operating costs. Additionally, we determine that gender and culture affect the pattern of contributions. We also find that individuals prefer to contribute to sustainable supplies, rather than to their ongoing operations. Our paper has practical implications for the financing of public goods through voluntary provisions.
Keywords: C73; C91; C92; H41; 330; differential games; experiment; public goods; voluntary provision